ASSESSMENT OF THE EFFECT OF A PROBIOTIC PREPARATION CONTAINING SACHAROMYCES BOULARDII ON THE INTESTINAL MICROBIOCENOSIS IN ACUTE INFECTIOUS DIARRHEA IN CHILDREN (Academia Science Repository, 2023)
This article describes the assessment of the effect of a probiotic preparation containing S. boulardii (CNCMI-745 strain) on the intestinal microbiocenosis in the complex treatment of children with acute infectious diarrhea still the age of 5 years.